THE EFFECT OF IMPLEMENTING INTELLECTUAL DEBATE PRACTICE AS A CRITICAL THINKING DEVELOPMENT ACTIVITY TO THE SENIOR HIGH SCHOOL STUDENTS OF ONE OF THE PUBLIC ISLAMIC SCHOOLS IN JAMBI - Ismail Ismail; Fardinal Fardinal; Fatonah Nurdin; Sudirman Anwar; Ahdiyenti Ahdiyenti; Rafik Darmansyah; Alisyah Pitri; Muhammad Yusuf (Dinasti Publisher, 2022)
Previous research or relevant research is very important in a research or scientific article. Based on previous research or relevant research, it certainly serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews how the influence of debate training as a critical thinking activity on the negotiation of the personal values ??of Muslim youth at a state Islamic secondary education institution in the city of Jambi, this research is a form of qualitative action research conducted in two cycles. The results of this action research show that: (1) participation in debate training as a critical thinking activity has an effect on Muslim youth's decision-making regarding their personal values; (2) there are five internal factors that influence the decision making of Muslim youth after the entire debate training cycle is completed; (3) there are five external factors that influence the decision making of Muslim youth after the entire cycle of debate training has been completed.